Dismantling the boundaries of the ECB's monetary policy mandate: The CJEU's OMT judgement and its consequences - Lars P. Feld; Clemens Fuest; Justus Haucap; Heike Schweitzer; Volker Wieland; Berthold U. Wigger (Stiftung Marktwirtschaft, 2016)
The German Federal Constitutional Court (Bundesverfassungsgericht) submitted an order for referral to the European Court of Justice (CJEU) in 2014, asking it to clarify the compatibility of the "Outright Monetary Transactions" (OMT)-Programme with European Union law. The OMT-Programme prepares the ground for the selective purchasing of government bonds of crisis-struck Member States of the European Monetary Union (EMU). A year later, the CJEU decided that the OMT-Programme is covered by the mandate of the European Central Bank (ECB) and does not violate the prohibition of the monetary financing of Member States. Concerns raised by the Federal Constitutional Court were only partially adressed. Now the ball has been passed back to the Federal Constitutional Court. In this study, the Kronberger Kreis, Scientific Council of the Stiftung Marktwirtschaft, explains why the CJEU's reasoning would have irreversable consequences, if the German Federal Constitutional Court were to follow. The CJEU's judgment dismantles the boundaries of the ECB's monetary policy mandate and significantly weakens the prohibition of the monetary financing of Member States in the long run. Effective judicial review of the scope of the ECB's competence would no longer be guaranteed. An act of crisis intervention by the ECB threatens to irrevocably turn the future structure of the EMU into the wrong direction. Nonetheless, the Federal Constitutional Court remains obliged to execute its ultra vires control in an EU-friendly manner. A rupture in the cooperative relationship between the German Federal Constitutional Court and the CJEU could have far-reaching consequences, especially considering the current crisis-riddled state of the EU. The Federal Constitutional Court may therefore want to follow the operative part of the CJEU's judgment, but base it on a different legal reasoning, so as to reserve itself the possibility for future judicial review of the acts of the ECB based on more demanding legal standards than those laid out by the CJEU.
Keywords: 330